The Australian Public is Still Vulnerable to Emerging Virulent Strains of West Nile Virus - Prow, Natalie A.; Hewlett, Elise K.; Faddy, Helen M.; Coiacetto, Flaminia; Wang, Wenqi; Cox, Tarnya; Hall, Roy A.; Bielefeldt-Ohmann, Helle (Frontiers in Public Health, 2014)
The mosquito-borne West Nile virus (WNV) is responsible for outbreaks of viral encephalitis in humans and horses with particularly virulent strains causing recent outbreaks in Eastern Europe, the Middle East and North America. In Australia, a strain of WNV, Kunjin (WNVKUN), is endemic in the north and infection with this virus is generally asymptomatic. However, in early 2011, following extensive flooding, an unprecedented outbreak of WNVKUN encephalitis in horses occurred in south-eastern Australia, resulting in more than 1,000 cases and a mortality of 10-15%. Despite widespread evidence of equine infections, there was only a single mild human case reported during this outbreak. To understand why clinical disease was seen in horses without similar observations in the human population, a serosurvey was conducted using blood donor samples from areas where equine cases were reported to assess level of flavivirus exposure. The seroprevalence to WNVKUN in humans was low before the outbreak (0.7%), and no significant increase was demonstrated after the outbreak period (0.6%). Due to unusual epidemiological features during this outbreak, a serosurvey was also conducted in rabbits, a potential reservoir host. Out of 675 animals, sampled across Australia between April 2011 and November 2012, 86 (12.7%) were seropositive for WNVKUN, with the highest prevalence during February of 2012 (28/145; 19.3%). As this is the first serological survey for WNVKUN in Australian feral rabbits, it remains to be determined whether wild rabbits are able to develop a high enough viraemia to actively participate in WNV transmission in Australia. However, they may constitute a sentinel species for arbovirus activity, and this is the focus of ongoing studies. Collectively this study provides little evidence of human exposure to WNVKUN during the 2011 outbreak and indicates that the Australian population remains susceptible to the emergence of virulent strains of WNV.